PERANCANGAN APLIKASI PEMESANAN LAUNDRY SECARA ONLINE BERBASIS ANDROID MENGGUNAKAN METODE PROTOTYPE - Arif Dian Pratama; Willis Puspita Sari (CV. Multi Kreasi Media, 2024)
In the current laundry business services, there are various obstacles that are often experienced by consumers experiencing problems in ordering laundry, namely customers who have ordered cannot know what laundry status is currently in the process. So if you want to know the status of your order, you usually have to use a phone or SMS. And if there are new customers who have never ordered these consumers, they must come to the place or call this laundry place to ask for information about the laundry service. To improve services in this laundry business in order to provide comfort and convenience in transactions. Then an android-based online laundry ordering application was designed which is expected to make it easier and provide convenience for Laila Laundry consumers.